Pengaruh Perpsepsi Kegunaan dan Persepsi Kemudahan Terhadap Kepuasan Pengguna Aplikasi MYBCA Dengan Kepercayaan Pengguna Sebagai Variabel Intervening - Dilla Nanda Putri, I Gusti Ayu; Purnama Dewi, Putu (Economic Reviews Journal, 2025)
This study aims to analyze the influence of perceived usefulness and perceived ease of use on user satisfaction of the MyBCA application, with user trust as an intervening variable. The research was conducted in Denpasar City, which has the highest number of mobile banking users in Bali. A quantitative approach was employed using a sample of 190 MyBCA users selected through multivariate sampling rules. Data were collected using a Likert-scale questionnaire and analyzed through Partial Least Squares (PLS) using SmartPLS 4.0. The results indicate that both perceived usefulness and perceived ease of use significantly affect user satisfaction and trust. User trust also shows a significant direct effect on satisfaction. Mediation testing further confirms that trust partially mediates the influence of perceived usefulness and perceived ease of use on satisfaction, emphasizing the importance of system reliability and security in strengthening user experience. These findings highlight that users value applications that are beneficial, easy to operate, and trustworthy. The study concludes that enhancing functionality, usability, system stability, and security features is essential for improving satisfaction and sustaining continued use of MyBCA.